MENGGALI JEJAK KULTURAL: UNSUR BUDAYA TRADISI TEDAK SITEN DALAM NOVEL HELLO KARYA TERE LIYE - Fatmawati, Tia Dwi; Ahmadi, Anas (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This article explores the intricate relationship between literature and culture through the lens of the Tedak Siten tradition, as depicted in the novel Hello by Tere Liye. Literature, as a mirror of societal life, reflects the values, traditions, and identities that shape communities, particularly in culturally diverse Indonesia. Using a non-interactive qualitative approach, this study analyzes cultural elements presented in the novel, such as rituals, traditional foods, and ceremonial tools. The Tedak Siten ritual is not merely a ceremonial event, but a profound cultural symbol representing communal hope and the social recognition of a child's growth. Furthermore, the use of traditional foods like tumpeng and culturally specific instruments reinforces collective identity. This study highlights the vital role of literature in preserving and promoting cultural heritage amid rapid modernization. It emphasizes how literary works can foster awareness, appreciation, and intergenerational transmission of local traditions. By examining Tere Liye’s narrative, this research contributes to cultural preservation efforts and underscores the importance of integrating cultural education into contemporary literary discourse.